Molecular study of transfusion dependent thalassemia patients who attended pediatric day care Hospital Universiti Sains Malaysia, Kelantan from January 2006 to April 2006. - Rozitah, Razman (2008)
Thalassemia has emerged as one of the most common public health problems in Malaysia, particularly among Malaysian Chinese and Malays. This study aims to determine the spectrum of Thalassaemia gene mutations found in transfusion dependent Thalassaemia patients who attended Pediatric Daycare Unit, Hospital Universiti Sains Malaysia, Kelantan, Malaysia. The findings are important for establishing the prenatal diagnosis in our Human Genome Centre.This is a cross sectional study in which 38 transfusion dependent Beta Thalassaemia patients were screened for six different mutations previously shown to be prevalent in the Malaysian population. Sampel collection was started in January, 2006 till April, 2006. DNA was extracted from leucocytes collected from the peripheral vein, amplified by PCR and digested by six restriction enzymes for detection of mutations. The mutation were correlated with the clinical severity based on the following clinical parameters : age at presentation, pre-transfusion hemoglobin level, mean volume of blood transfusion per kilo body weight per year, spleen size, spleenectomy and growth failure were recorded in these patients to determine the severity of each group of thalassaemia type depicted by the mutation. For the statistical analysis, Kruskal-Wallis test and univariate analysis were used.